2021
DOI: 10.3892/etm.2021.10472
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic regulation of imbalance‑induced myocardial fibrosis and its mechanism in rats with cirrhosis

Abstract: The aim of the present study was to investigate the changes in cardiac function and myocardial damage in rats with cirrhosis. In addition, a secondary aim was to explore any potential changes in the expression levels of β1-adrenergic (β1) and muscarinic acetylcholine (M2) receptors . A cirrhotic cardiomyopathy (CCM) rat model was established by CCL4-oil solution for subcutaneous injection into the neck. Pathological changes in the liver and myocardial tissues were detecting by H&E staining and Masson trichrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Currently, it is understood that exogenous IL-2 can enhance the response of regulatory T cells and inhibit brosis, while the function of endogenous IL-2 remains unclear [23,24]. The ndings of this study revealed an increase in protein levels of TNF-α and PTGS2 in the myocardial tissue of MF rats, accompanied by a decrease in IL-2 protein levels.…”
Section: Discussionmentioning
confidence: 65%
“…Currently, it is understood that exogenous IL-2 can enhance the response of regulatory T cells and inhibit brosis, while the function of endogenous IL-2 remains unclear [23,24]. The ndings of this study revealed an increase in protein levels of TNF-α and PTGS2 in the myocardial tissue of MF rats, accompanied by a decrease in IL-2 protein levels.…”
Section: Discussionmentioning
confidence: 65%
“…This suggests that the positive contractile response β-adrenergic and negative contractile response to M2-receptor are attenuated in cirrhotic hearts compared with controls (Jaue et al, 1997). A recent study demonstrated that both β1 and M2 receptor protein expressions are decreased in the myocardial tissues from cirrhotic rats induced by carbon tetrachloride (Yu et al, 2021). The difference might be due to the nature of liver injury in the animal models.…”
Section: M2-muscarinic Receptormentioning
confidence: 98%
“…The role of the microbiota in mediating cardiac disease outcomes has also been evaluated with studies finding perturbations in microbial content and metabolites potentially able to mediate cardiac dysfunction and thus overall cardiovascular disease outcomes (Beale et al, 2021). Taken together, the intra-abdominal changes associated with portal hypertension including mesenteric ischemia, alterations in gut barrier function with increase in intestinal permeability, luminal bacterial overgrowth and ultimately translocation of bacteria and or bacteria derived products that result in endotoxemia, can potentially lead to an elevation of systemic pro-inflammatory cytokines including, but not limited, to tumor necrosis factor alpha (TNFα), interleukin 1β (IL-1β) and interleukin-6 (IL-6) (Liu et al, 2000;Yu et al, 2021), that can then mediate downstream cardiac dysfunction. Currently there is a paucity of both experimental and clinical data evaluating the role of the microbiota in cirrhosis associated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an autopsy study has shown ventricular hypertrophy, cardiac valve calcification, interstitial edema, fibrosis in myocytes, and coronary artery atherosclerosis in cirrhotic patients [ 65 ]. Cardiomyopathy as systolic and diastolic abnormalities, inotropic and chronotropic dysfunction, increased plasma levels of myocardial enzymes, myocyte swelling and hypertrophy, and gross abnormalities in cardiomyocytes in histological examinations have also been reported in animal models of cirrhosis and HE [ 66 , 67 , 68 , 69 ]. Reduced response to vasoconstrictors and accumulation of circulatory vasodilators, such as nitric oxide, carbon monoxide, and endocannabinoids explain the suppression of systemic vascular resistance in liver failure [ 70 , 71 , 72 , 73 ].…”
Section: Factors That May Indirectly Affect the Efficacy Of Glymphati...mentioning
confidence: 99%